Deep Fungal Infection- An Emerging Problem in Bangladesh - Parvin, Rukhsana; Amin, Robed; Mahbub, Md Shahriar; Hasnain, Muntasir; Arif, Khan Mohammad; Miah, Md Titu; Gupta, Ratan Das; Alam, Md Billal; Ahasan, HAM Nazmul (Journal of Medicine, 2010)
Objective: Invasive deep fungal infections have become a major cause of morbidity and mortality over the past three decades. Organ transplantation, the use of aggressive chemotherapy and the availability and widespread use of immunosuppressive treatments for many medical ailments have resulted in large populations of patients who are at risk of fungal infections. We report our experience to increase awareness of the clinical spectrum of disseminated fungal infection and its similarity to other infections and malignancy. Materials and Methods: Case reports from different medical institution for last 6 months were searched through case registry and recent scientific presentation and publications. Results: Recently a case of Histoplasmosis was reported in Dhaka Medical College Hospital (DMCH) where a 57 years old male presented with low grade fever for 3 months, backache followed by progressive weakness of both lower limbs , there was spastic paraplegia with sensory loss upto the level of D10. An open biopsy from paravertebral soft tissue showed histopathological features consistent with histoplasmosis. Other deep fungal infections e.g. pulmonary blastomycoses, mucormycoses and pulmonary aspergilloma were also reported in DMCH and Bangabandhu Shiekh Mujib Medical University (BSMMU) and RMCH. Conclusion: As these fungal infections are not commonly encountered in our country and most of the dissemination has similar clinical features of chronic inflammatory process and malignancy, we need a high index of suspicion to diagnose with different diagnostic approach. Bangladesh may be experiencing increase load of disseminated fungal infections and awareness is now very important to explore its underlying aetiology. Keywords: Endemic mycoses; histoplasmosis; blastomycosis; mucormycosis; aspergilloma; Bangladesh DOI: 10.3329/jom.v11i2.5466 J MEDICINE 2010; 11 : 170-175